2004
DOI: 10.1016/j.clpt.2004.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine metabolite ratio as an index of cytochrome P450 2A6 metabolic activity*1

Abstract: The 3HC/COT ratio derived from nicotine either administered as a probe drug or from tobacco use, measured in either plasma or saliva, is highly correlated with the oral clearance of nicotine. The ratio appears to be a useful noninvasive marker of the rate of nicotine metabolism (which is important in studying nicotine addiction and smoking behavior), as well as a general marker of CYP2A6 activity (which is important in studying drug and toxin metabolism).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
453
3
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(477 citation statements)
references
References 24 publications
9
453
3
4
Order By: Relevance
“…Analysis may be carried out on as little as 20 µl of plasma and the limits of quantitation for d 2 -cotinine and d 2 -nicotine were 0.25 ng/ml and 0.15 ng/ml, respectively. These limits are similar to what has been reported previously for the analysis of d 2 -cotinine in plasma by APCI LC/MS/MS [14]. The method is being applied to on-going studies of nicotine metabolism in smokers and non-smokers administered d 2 -nicotine.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Analysis may be carried out on as little as 20 µl of plasma and the limits of quantitation for d 2 -cotinine and d 2 -nicotine were 0.25 ng/ml and 0.15 ng/ml, respectively. These limits are similar to what has been reported previously for the analysis of d 2 -cotinine in plasma by APCI LC/MS/MS [14]. The method is being applied to on-going studies of nicotine metabolism in smokers and non-smokers administered d 2 -nicotine.…”
Section: Discussionsupporting
confidence: 83%
“…determination of serum cotinine concentrations [13] has been applied to the analysis of d 2 -cotinine [14][15][16]. Two of these studies also quantified urine concentrations of d 2 -nicotine by LC/MS/MS [15;16], but GC/MS analysis was used to quantify plasma d 2 -nicotine, suggesting that the LC/MS/MS method used was not sufficiently sensitive for the analysis of the lower d 2 -nicotine concentrations in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…173 CYP2A6 is located on chromosome 19 (19q13.2) and a nearby region was associated with smoking frequency (X1 cigarette per day) in a genome-wide linkage scan. 39 Large interindividual and interethnic variations in CYP2A6 activity have been reported; [170][171][172][174][175][176][177] this variability is mainly attributed to the large genetic variations in CYP2A6. 178,179 A brief summary of how genetic variations in CYP2A6 affect smoking behaviors will be provided here as a detailed review was recently published.…”
Section: Other Likely Candidates Involved In Neurotransmitter Systemsmentioning
confidence: 99%
“…A first proof was provided by Dempsey et al, who administered deuterium labeled nicotine and cotinine to 62 healthy volunteers. Resulting trans 3'-OH-cotinine/cotinine ratios in oral fluid 6 h post-intake were highly correlated with several indices of CYP2A6 activity, including 6 h ratios in plasma and oral clearance of both nicotine and cotinine [111]. CYP2A6 phenotyping based on trans 3'-OH-cotinine/cotinine ratios originating from nicotine in tobacco smoke was examined by St. Helen et al Regression analysis revealed high correlations between ratios in oral fluid and both whole blood and plasma of smokers and nonsmokers exposed to tobacco smoke.…”
Section: Oral Fluidmentioning
confidence: 93%